The Use of Wattpad Application for Reading Skill in EFL Classroom - Aini, Nurul; Pambudi, Lutfia Arum; Nisa, Aulia (Celebes Scholar pg, 2024)
The objective of this study was to investigate the attitudes around the use of the Wattpad application as a tool for enhancing reading skills within the context of English as a Foreign Language (EFL) classrooms. The present study used a quantitative research methodology. The researcher administered a questionnaire to a group of students on their use of the Wattpad program. The participants in this research consisted of students enrolled in the English department at IAIN Kediri. The study sample consisted of 30 students from the English department. The findings indicate that 70% of respondents selected the option for item number 1. The use of the Wattpad application for enhancing reading skills in the English as a Foreign Language (EFL) classroom has been shown to have a beneficial impact. The conclusive findings of a questionnaire, including a total of 10 elements, indicated a majority agreement among participants. The Wattpad program may be deemed a valuable tool for enhancing reading proficiency in the English as a Foreign Language (EFL) classroom. The Wattpad program serves as a valuable tool for English language acquisition, offering students an enjoyable and engaging learning experience that mitigates feelings of boredom. The empirical evidence suggests that Wattpad serves as a proficient instrument for facilitating language acquisition. The use of the Wattpad program has shown to be a beneficial method for enhancing kids' reading proficiency.